Inpatient treatment for eating disorders : patients' experiences, demographics, and treatment characteristic - Móeiður Pálsdóttir 1990- (2022)
Eating disorders are complex problems and are often difficult to treat. Inpatient hospital treatment for eating disorders is often required when there is significant medical or psychological instability or when outpatient treatment is not working. There are few studies on inpatient treatment for eating disorders in Iceland, and no studies were found on the patients' experience of the treatment. The study aimed to investigate patients' experiences with inpatient treatment for eating disorders, demographics, and treatment characteristics between the years 2009 to 2021. The study uses both quantitative and qualitative methods. Data were collected from medical records, and a total of 107 patients were admitted for inpatient treatment for 164 hospitalizations. A total of 58 children and 50 adults were admitted, with only one patient being admitted as a child and an adult. Six adult participants were interviewed and answered the EDE-Q questionnaire and the Quality of Life scale. Most of the patients were females diagnosed with anorexia nervosa and were admitted once to inpatient treatment. Weight and BMI increased on average during treatment for both adults and children. The results from the qualitative analysis have practical and clinical value. The findings suggest that having a detailed meal plan and adhering to it during meal support, increasing psychological treatment, and educating staff members on eating disorders would be valuable changes and improve the inpatient treatment. Keywords: eating disorders, inpatient treatment, thematic analysis